The Professional Guinea Pig : Big Pharma and the Risky World of Human Subjects - Abadie, Roberto (Book collections on Project MUSE., 2010)
Ethnography of the lives of a new professional drug testing class, analyzing the underground economy of human research subjects (guinea pigs) who test the safety of new drugs for money (illegal immigrants, homeless people, ex-convicts, anarchists, and oth.